Structure-reactivity relationship of acrylic acid ester ether dimers in ATRP - Kocasakal, Gülhan. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2007., 2007)
Aliphatic cyclopolymers synthesized by the cyclopolymerization of alkyl {460}- (hydroxymethyl)acrylate ether dimers have high thermal stabilities, high glass transition temperatures and show limited shrinkage during polymerization. Cyclopolymerizations of RHMA ether dimers by ATRP have been previously investigated in the literature for three different alkyl groups: ethyl, n-butyl and tert-butyl groups. It was found that as the bulkiness of the substituent group increased cyclization efficiency also increased. However, ATRP cyclopolymerization has not been investigated with dimers that contain bulkier substituents. It is known that cyclization efficiency in conventional free radical polymerization is higher for adamantyl {460}-(hydroxymethyl)acrylate ether dimer than the ones containing smaller alkyl groups such as ethyl, t-butyl. However, the effect of such bulky groups on the ATRP process was unknown. Therefore, ATRP’s of more bulky RHMA ether dimers such as adamantyl and cyclohexyl {460}-(hydroxymethyl)acrylate ether dimers were investigated. CuBr/PMDETA was employed as the catalyst complex and polymerizations were carried out in xylene. The results showed that, highly cyclized soluble aliphatic cyclopolymers could be obtained by the ATRP process with both monomers. However, the polydispersities of the cyclopolymers obtained were higher than the cyclopolymers obtained with the t-butyl derivative, indicating that the ATRP process was less controlled with bulkier groups. The livingness of the cyclopolymers was checked by the copolymerization studies with n-butyl and t-butyl acrylate comonomers where the cyclopolymers obtained were used as macroinitiators. Results suggest that cyclopolymers were living, however, copolymers obtained had high polydispersities most probably due to the slow initiation from the cyclic backbone. Preliminary studies on the physical properties of the cyclopolymers were also carried out.
Keywords: Cyclopolymerization.